Senescence-related genes and proteins in the development of Alzheimer’s disease: evidence from transcriptomic and Mendelian randomization analysis - Liu, Ying; Chen, Jiao (Frontiers in Aging Neuroscience, 2024)
Purpose Alzheimer’s disease (AD) is a common neurodegenerative disease, which can lead to cognitive impairment and dementia. Since AD is tightly associated with aging and cellular senescence, objective of this study was to investigate the association between senescence-related genes and proteins (SRGs and SRPs) and the development of AD. Design The whole study was based on transcriptomic analysis of control and AD brain tissues and Mendelian randomization (MR) analysis. Methods For transcriptomic analysis, GSE5281 dataset from GEO database contains the transcriptomic data of human brain tissues (n = 161) from control group and AD patients. The expression of SRGs in control and AD brain tissues were compared by Student’s t test. For MR analysis, the instrumental single-nucleotide polymorphisms (SNPs) associated with 110 SRPs were filtered and selected from a large genome-wide association study (GWAS) for plasma proteome. The causality between plasma levels of SRPs and AD was explored using GWAS data of AD from Lambert et al. (17,008 cases and 37,154 controls) and further validated by using data from FinnGen consortium (6,489 patients and 170,489 controls). MR estimate was performed using the inverse-variance weighted (IVW) method and the heterogeneity and pleiotropy of results were tested. Results Transcriptomic analysis identified 36 up-regulated (including PLAUR) and 8 down-regulated SRGs in AD brain tissues. In addition, the MR results at both discovery and validation stages supported the causality between plasma levels of PLAUR (IVW-p = 3.04E-2, odds ratio [OR] = 1.15), CD55 (IVW-p = 1.56E-3, OR = 0.86), and SERPINE2 (IVW-p = 2.74E-2, OR = 0.91) and the risk of AD. Conclusion Our findings identified that PLAUR, as an SRG, may take part in the development of AD and found that high plasma levels of PLAUR was associated with increased risk of AD, indicating that this gene was a risk factor for this disease and providing the rationale of existing drugs or new preventative and therapeutic strategies.